Heterogeneous asymmetric epoxidation of alkenes catalysed by a polymer-bound (pyrrolidine salen)manganese(III) complex - Song, CE; Roh, EJ; Yu, BM; Chi, DY; Kim, SC; Lee, KJ (ROYAL SOC CHEMISTRY, 2000)
Excellent enantioselectivity (e.g. 92% ee for 2,2-dimethylchromene) has been achieved in heterogeneous asymmetric epoxidation using a polymer-bound (pyrrolidine salen)-manganese(III) complex; however, this polymeric catalyst underwent partial decomposition under epoxidation conditions.
Keywords: ENANTIOSELECTIVE EPOXIDATION; OLEFINS